2019
DOI: 10.1063/1.5118258
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously imaging and quantifying in vivo mechanical properties of crystalline lens and cornea using optical coherence elastography with acoustic radiation force excitation

Abstract: The crystalline lens and cornea comprise the eye’s optical system for focusing light in human vision. The changes in biomechanical properties of the lens and cornea are closely associated with common diseases, including presbyopia and cataract. Currently, most in vivo elasticity studies of the anterior eye focus on the measurement of the cornea, while lens measurement remains challenging. To better understand the anterior segment of the eye, we developed an optical coherence elastography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…The back-reflected light from the compensation arm is detected by the second channel of the balanced photodetector to offset the DC component of the generated interference fringes. A balanced photodetector with a bandwidth from 30 kHz to 1.6 GHz was selected to minimize timing jitters to enhance the phase stability and to enable a long imaging range for retrieving the two OCT interference fringes from different frequency domains 14 .…”
Section: System Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…The back-reflected light from the compensation arm is detected by the second channel of the balanced photodetector to offset the DC component of the generated interference fringes. A balanced photodetector with a bandwidth from 30 kHz to 1.6 GHz was selected to minimize timing jitters to enhance the phase stability and to enable a long imaging range for retrieving the two OCT interference fringes from different frequency domains 14 .…”
Section: System Setupmentioning
confidence: 99%
“…Most OCE systems utilizing the acoustic radiation force (ARF) as a tissue excitation method are reported to have the capability of detecting displacements in the range of hundreds of nanometers. In those cases, a relatively strong ARF is necessary to accurately reconstruct the elastic wave propagation, and this force may exceed the ophthalmic mechanical index (MI) safety standard of 0.23 approved by the Food and Drug Administration [13][14][15] . An OCE system with ultrahigh displacement sensitivity will be able to scale down the applied ARF by at least 1 order of magnitude while maintaining a sufficient signal-tonoise ratio (SNR), which will reduce the required ARF such that it is within the range of the MI safety standard to facilitate the clinical translation of OCE in ophthalmology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) Spatial distribution of the cilia beating frequency at 23 C, 26 C, 29 C, and 33 C in which temperature has a positive impact on ciliary activity. Adapted from References [86,87] simultaneously assess the elasticities of the crystalline lens and the cornea in vivo (as shown in Figures 11A-C) [95]. For elasticity measurement of posterior eye, Qu et al reported the first in vivo quantitative elasticity map of the retina by displacement measurement (ie, the compression approach) in which a difference was demonstrated between healthy and damaged rabbit retina in 2018 [45].…”
Section: Optical Coherence Elastographymentioning
confidence: 99%
“…To address this issue, various intravascular imaging technologiesincluding optical coherence tomography (OCT), ultrasound (US), near-infrared°uorescence (NIRF), photoacoustic (PA), and optical coherence elastography (OCE)have been developed to characterize the thin¯brous cap, lipid pool, localized in°ammation, and biomechanical properties related to atherosclerotic plaques by quantifying the layered architecture, compositional data, and mechanical properties of coronary arteries. 2,[6][7][8][9][10][11][12][13][14][15][16][17]75 Intravascular ultrasound (IVUS) is the most commonly used clinical imaging technique for plaque diagnostics. 18,19 IVUS can provide crosssectional structural images of the coronary vessel with a resolution of 100 m and an imaging depth of 7 mm.…”
Section: Introductionmentioning
confidence: 99%